Analisis Faktor-Faktor Yang Mempengaruhi Generasi Z Dalam Konsumsi E-Wallet Saat Pandemi Covid-19 (Studi Pada Mahasiswa Aktif Program Sarjana di Kota Malang) - Ninggar, Aurellia Dara; Anggraini, Ika Khusnia (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study was conducted to determine the effect of convenience, promotion and lifestyle variables on generation Z e-wallet consumption (active undergraduate students) during the COVID-19 pandemic in Malang City. The analytical model used in this study is multiple linear regression analysis based on Ordinary Least Squares (OLS) using the SPSS Statistics 26 application which uses primary data obtained from the distribution of online questionnaires and then processed first from ordinal data using the Method of Successive Interval (MSI) into interval data with a quantitative research approach. Produced an analysis that the convenience, promotion and lifestyle variables had a positive and significant influence on the consumption of e-wallet generation Z (active undergraduate students) during the covid-19 pandemic in Malang City.Keywords: E-Wallet Consumption, Generation Z, Covid-19 Pandemic.